Psychological well-being as a driver of MSMEs performance: Insights from Tangkahan ecotourism - Prayudi, Ahmad; Pratiwi, Henny; Aulia, Muhammad Reza; Sari, Warsani Purnama; Syauqi, Teuku Muhammad; Fuqara, Fantashir Awwal; Yuhendra, Alfis (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to explore the relationship between job satisfaction, mental health, motivation, stress management, and performance of MSME actors engaged in the Tangkahan ecotourism sector. The main focus of this study is to understand what psychological factors and working conditions contribute the most to improving the performance of MSMEs in the sector. Methodology/approach: This study involved 117 MSME participants from university and government training programs. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) and supported by field observations to validate and strengthen the obtained quantitative finding. Results/findings: The study found that job satisfaction and mental health positively and significantly affect MSME performance, while motivation shows no significant impact. Psychological conditions and work environment play greater roles. Stress management indirectly enhances performance by improving mental health, despite its insignificant direct effect on performance. Conclusion: This study concludes that psychological well-being and job satisfaction are key factors in improving the performance of MSME actors in the ecotourism sector. Therefore, it is important for stakeholders to create a mentally supportive work environment and implement effective stress management strategies to optimize the productivity of MSMEs. Limitations: This study has limitations in the geographical scope and characteristics of the respondents, which only includes MSME actors in the Tangkahan ecotourism area. Therefore, the results of this study cannot be generalized to other MSME regions or sectors. Contribution: This study contributes to MSME empowerment policy by emphasizing mental health and job satisfaction improvement. The findings guide universities, governments, and institutions in designing effective interventions to enhance MSME actors’ productivity and overall performance.